PERAN GURU AKIDAH AKHLAK DALAM MEMBENTUK KARAKTER JUJUR PADA SISWA DI MTsN 15 JOMBANG - Bagus Pangestu, Putra; Kibtiyah, Asriana; Syamsudin (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2023)
Abstract: Since the learning process is at the center of the whole educational process, the function of the moral creed instructor is a very important deciding element in education generally. It is believed that the morality instructor would help pupils develop better morals so they would behave well, especially by being honest. In order to build honest character in pupils at MTsN 15 Jombang, this study looked at the function of the instructor's core moral beliefs for supporting and impeding aspects of the teacher. This researcher does fieldwork using a descriptive-qualitative methodology. Utilizing procedures such as interviews, observation, and documentation, data was gathered using a natural backdrop as a direct data source. Domain analysis is the method used for data analysis. employing references to validate the triangulation data's accuracy. This study have a result that the Akidah Akhlak instructor serves as a teacher, mentor, educator, and class manager. The Akidah Akhlak instructor has a strategic function in helping pupils develop honest character through this position. Professional educators and the presence of a family and community environment are supportive factors, whereas a lack of parental involvement, student ignorance, student egotism, and community environmental factors and their associations are inhibiting.